Scenes from an automotive wonderland : remarkable cars spotted in postwar Europe - Cagle, Gregory A. (McFarland & Company, Inc., Publishers, 2018)
"Gregory Cagle was a 10 year-old car fanatic when his family moved from New Jersey to Germany in 1956. For the next five years he photographed unusual, rare and sometimes bizarre automobiles throughout Europe. This book features 105 specimens of auto exotica, captured with Cagle's Iloca Rapid-B 35mm camera"--